EFFECT OF HERBAL DETERGENT BASED DABUR VATIKA SHAMPOO ON GUPPY POECILIA RETICULATA (PETERS) - K. A. AHAD NAJAM; WANULE D. D. C. S. BHOWATE (The Bioscan, 2010)
The fish Poecilia reticulate (Peters) is well known natural biological control agent for mosquito larvae. Poecilia reticulata is released by Municipal Corporations in order to control of mosquito larvae, in different water bodies. Indiscriminate use of shampoos and detergents cause water pollution. The present investigation is discus the effect of herbal detergent based Vatika shampoo on the mortality and behavioural changes of guppy fish; Poecilia reticulata (Peters).